Interaction between the STAT4 rs11889341(T) risk allele and smoking confers increased risk of myocardial infarction and nephritis in patients with systemic lupus erythematosus. Issue 9 (25th March 2021) - Reid, Sarah; Hagberg, Niklas; Sandling, Johanna K; Alexsson, Andrei; Pucholt, Pascal; Sjöwall, Christopher; Lerang, Karoline; Jönsen, Andreas; Gunnarsson, Iva; Syvänen, Ann-Christine; Troldborg, Anne Margrethe; Voss, Anne; et al.
Abstract : Objective: To investigate how genetics influence the risk of smoking-related systemic lupus erythematosus (SLE) manifestations. Methods: Patients with SLE (ndiscovery cohort =776, nreplication cohort =836) were genotyped using the 200K Immunochip single nucleotide polymorphisms (SNP) Array (Illumina) and a custom array. Sixty SNPs with SLE association (p<5.0×10 −8 ) were analysed. Signal transducer and activator of transcription 4 (STAT4) activation was assessed in in vitro stimulated peripheral blood mononuclear cells from healthy controls (n=45). Results: In the discovery cohort, smoking was associated with myocardial infarction (MI) (OR 1.96 (95% CI 1.09 to 3.55)), with a greater effect in patients carrying any rs11889341 STAT4 risk allele (OR 2.72 (95% CI 1.24 to 6.00)) or two risk alleles (OR 8.27 (95% CI 1.48 to 46.27)). Smokers carrying the risk allele also displayed an increased risk of nephritis (OR 1.47 (95% CI 1.06 to 2.03)). In the replication cohort, the high risk of MI in smokers carrying the risk allele and the association between the STAT4 risk allele and nephritis in smokers were confirmed (OR 6.19 (95% CI 1.29 to 29.79) and 1.84 (95% CI 1.05 to 3.29), respectively). The interaction between smoking and the STAT4 risk allele resulted in further increase in the risk of MI (OR 2.14 (95% CI 1.01 to 4.62)) and nephritis (OR 1.53 (95% CI 1.08 to 2.17)), with 54% (MI) and 34% (nephritis) of the risk attributable to the interaction. Levels of interleukin-12-induced phosphorylation of STAT4 in CD8+ T cells were higher in smokers than in non-smokers (mean geometric fluorescence intensity 1063 vs 565, p=0.0063). Lastly, the IL12A rs564799 risk allele displayed association with MI in both cohorts (OR 1.53 (95% CI 1.01 to 2.31) and 2.15 (95% CI 1.08 to 4.26), respectively). Conclusions: Smoking in the presence of the STAT4 risk gene variant appears to increase the risk of MI and nephritis in SLE. Our results also highlight the role of the IL12−STAT4 pathway in SLE-cardiovascular morbidity.